This Mine is Mine! How Minerals Fuel Conflicts in Africa - Nicolas Berman; Mathieu Couttenier; Dominic Rohner; Mathias Thoenig (Center for Economic Studies and ifo Institute (CESifo), 2015)
We combine original geo-referenced data on mining extraction of 15 minerals with information on conflict events at spatial resolution of 0.5o x 0.5o for all Africa over 1997-2010. Exploiting exogenous variations in world prices, we find a positive impact of mining on conict at the local level. Quantitatively, the historical rise in prices (commodity super-cycle) explains 15-25 percent of average country-level violence in Africa. We then document how the appropriation of a mining area by a fighting group contributes to the escalation from local to global violence. Finally, we analyze the impact of corporate practices and transparency initiatives in the mining industry.
Keywords: C23; D74; Q34; 330; minerals; mines; conflict; fighting; natural resources; rebellion